2017
DOI: 10.1021/acs.energyfuels.7b02948
|View full text |Cite
|
Sign up to set email alerts
|

New Coupled Apparent Permeability Models for Gas Transport in Inorganic Nanopores of Shale Reservoirs Considering Multiple Effects

Abstract: The study of seepage mechanism in shale gas reservoir has been paid more and more attention. The shale gas reservoirs are rich in nanosized pores. The pores in shale matrix can be divided into organic nanopores and inorganic nanopores. At present, there are many literature studies focusing on establishing a model to analyze the gas transport mechanism in shale organic pores. Some researchers also considered the difference of gas transport in organic and inorganic matrix pores, and a mathematical model of inorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…In contrast, on the basis of relative mature theory and reasonable assumptions, a lot of analytical models have been proposed to capture multiple gas flow mechanisms or fluid storage modes inside both shale organic/inorganic matrix, encompassing gas adsorption, surface diffusion, water distribution features, wall roughness (Sheikholeslami et al, 2020(Sheikholeslami et al, , 2021a(Sheikholeslami et al, , 2021b. Notably, each theoretical model has its own applicable criterions or suitable conditions and may fail to generate desirable results, particularly at nanoscale pores (Bao et al 2017a(Bao et al , 2017bWang et al 2017). As a result, the analytical models, coupling classic theories and multiple key flow mechanisms, inevitably suffer limitations for practical application toward realistic cases.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, on the basis of relative mature theory and reasonable assumptions, a lot of analytical models have been proposed to capture multiple gas flow mechanisms or fluid storage modes inside both shale organic/inorganic matrix, encompassing gas adsorption, surface diffusion, water distribution features, wall roughness (Sheikholeslami et al, 2020(Sheikholeslami et al, , 2021a(Sheikholeslami et al, , 2021b. Notably, each theoretical model has its own applicable criterions or suitable conditions and may fail to generate desirable results, particularly at nanoscale pores (Bao et al 2017a(Bao et al , 2017bWang et al 2017). As a result, the analytical models, coupling classic theories and multiple key flow mechanisms, inevitably suffer limitations for practical application toward realistic cases.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al , established a mathematical model to quantify the thickness of the water film at certain relative humidity conditions and demonstrated that the water film decreases the flow volume of methane in hydrophilic nanopores. On this basis, Sun et al, Wang et al, and Li et al developed corresponding permeability models for gas flow in hydrophilic nanopores by accounting different factors such as cross-sectional shapes, confinement effect, and moisture content. They pointed out that initial water saturation significantly decreases the effective permeability of methane.…”
Section: Introductionmentioning
confidence: 99%
“…pointed out that the permeability of methane flow in hydrophilic nanopores reduces about 15–30% with 30% water saturation. Although considerable progresses have been achieved on gas–water two-phase flow in nanopores by these analytical studies, most of the current flow models merely considered the ideal super-hydrophilic nanopores, where the water film is assumed as the extension of the walls. The effect of water film on the gas–walls interactions are universally neglected as well.…”
Section: Introductionmentioning
confidence: 99%
“…241 To accurately estimate formation properties and shale gas production forecasts, various studies report permeability models coupled to mechanical effects. [242][243][244][245][246][247] Liehui, et al 238 compared the different models and found that the Palmer and Mansoori 248 model is suitable to describe permeability variations of a shale gas well over its entire production life span. Because of gas desorption in shale gas reservoirs, shale matrix shrinkage progressively occurs but particularly during the late production stage which can lead to an increase in permeability.…”
Section: Review Energy and Environmental Sciencementioning
confidence: 99%